2021
DOI: 10.1177/10245294211003864
|View full text |Cite
|
Sign up to set email alerts
|

Secular stagnation and core-periphery uneven development in post-crisis eurozone

Abstract: In this paper, we analyse secular stagnation in the eurozone. We adopt a core-periphery perspective and analyse whether the 2007–2008 financial crisis triggered off diverging dynamics in the growth potential of core and peripheral eurozone countries. We find that secular stagnation affects the whole eurozone but is a much more serious concern in the periphery. Among the components of potential GDP, the NAIRU in particular has diverged since 2008. We find that the increase in the NAIRU is strongly related to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…This result is consistent with other C-P analysis in Europe focused on variables such as GDP or unemployment. Botta and Tippet (2022) even show a greater divergence from 2008. The originality of our contribution lies in the comparative analysis of productivity and wages, which sheds light on one of the main mechanisms that explains increasing inequality after the crisis.…”
Section: Productivity and Wage Evolutionmentioning
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with other C-P analysis in Europe focused on variables such as GDP or unemployment. Botta and Tippet (2022) even show a greater divergence from 2008. The originality of our contribution lies in the comparative analysis of productivity and wages, which sheds light on one of the main mechanisms that explains increasing inequality after the crisis.…”
Section: Productivity and Wage Evolutionmentioning
confidence: 92%
“…Our first above-cited aim is not entirely original; there are other contributions (more or less recent) that have discussed the validity of C-P analysis for studying uneven development in the world economy (Di Filippo, 1998; Ebenau 2012; Fischer, 2015) or within the EU (Botta and Tippet, 2022; Celi et al, 2018; Gambarotto and Solari, 2015; Weissenbacher, 2017). Our article is framed by this literature, and we establish a dialogue with previous contributions in order to identify key elements not yet considered for a C-P analysis of the EU.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research on the core-periphery structure in the European market found a clear downward trend of active banks in 2008 [24,27]. This is because foreign bank interactions with the Italian banks, for instance, had significantly dropped during the crisis.…”
Section: European Marketmentioning
confidence: 99%